The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1521/bumc.66.3.241.23366
|View full text |Cite
|
Sign up to set email alerts
|

Exploring psychological abuse in childhood: II. Association with other abuse and adult clinical depression

Abstract: A new retrospective interview assessment of childhood psychological abuse, an extension to the Childhood Experience of Care and Abuse (CECA) instrument, is described in a companion article (Moran, Bifulco, Ball, Jacobs, & Benaim, 2002). The purpose of the present article is to examine the relationship of childhood psychological abuse to other adverse childhood experiences and to major depression and suicidal behavior in adult life. Childhood experience and lifetime disorder were assessed retrospectively in a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
119
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 29 publications
11
119
0
11
Order By: Relevance
“…Nos 51 estudos epidemiológicos encontrouse que 14 destes (27,5%) são exclusivos com amostra do sexo feminino 14,15,16,17,18,19,20,21,22,23,24,25,26,27 . Em relação à idade dos entrevistados, 35 artigos (68,6%) utilizaram como amostra de pesquisa a faixa etária dos adultos e 16 artigos (31,4%), adolescentes e crianças 10,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Nos 51 estudos epidemiológicos encontrouse que 14 destes (27,5%) são exclusivos com amostra do sexo feminino 14,15,16,17,18,19,20,21,22,23,24,25,26,27 . Em relação à idade dos entrevistados, 35 artigos (68,6%) utilizaram como amostra de pesquisa a faixa etária dos adultos e 16 artigos (31,4%), adolescentes e crianças 10,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41 .…”
Section: Resultsunclassified
“…O estudo de violência psicológica como fator de risco, encontrado em 7 artigos (13,7%), apontam para bulimia nervosa, obesidade, ansiedade, depressão, estresse pós-traumático e distúrbios somáticos 21,22,27,28,55,56,57 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Also works of Hund and Espelage (2006) point to presence of correlation between emotional violence in childhood and eating disorders in the later life. In the study of Bifulco et al (2002), emotional violence experiences in childhood was related to suicidal behaviors in later life. However, Moran et al (2004) found relationship between emotional violence experiences and substance using by adolescents, but it was the weakest-in comparison with other analyzed types of violence.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong link between a history of childhood emotional abuse and diagnosis of depression in adulthood 8 , so as to 42% of the adults who have experienced early sexual abuse developed chronic depression 9 . There are a growing number of longitudinal studies relating childhood emotional abuse as development of symptoms and depressive episodes 10 .…”
Section: Introductionmentioning
confidence: 99%